Cloning and characterization of the Type I Baeyer–Villiger monooxygenase from Leptospira biflexa - Ceccoli, Romina Denis (2017)
Baeyer–Villiger monooxygenases are recognized by their ability and high selectivity as oxidative biocatalysts for the generation of esters or lactones using ketones as starting materials. These enzymes represent valuable tools for biooxidative syntheses since they can catalyze reactions that otherwise involve strong oxidative reagents. In this work, we present a novel enzyme, the Type I Baeyer–Villiger monooxygenase from Leptospira biflexa. This protein is phylogenetically distant from other well-characterized BVMOs. In order to study this new enzyme, we cloned its gene, expressed it in Escherichia coli and characterized the substrate scope of the Baeyer–Villiger monooxygenase from L. biflexa as a whole-cell biocatalyst. For this purpose, we performed the screening of a collection of ketones with variable structures and sizes, namely acyclic ketones, aromatic ketones, cyclic ketones, and fused ketones. As a result, we observed that this biocatalyst readily oxidized linear- and branched- medium-chain ketones, alkyl levulinates and linear ketones with aromatic substituents with excellent regioselectivity. In addition, this enzyme catalyzed the oxidation of 2-substituted cycloketone derivatives but showed an unusual selection against substituents in positions 3 or 4 of the ring.